2022
DOI: 10.3390/cells11132051
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Intermittent Hypoxia Increases Cell Proliferation in Hepatocellular Carcinoma

Abstract: Obstructive sleep apnea (OSA) syndrome is characterized by chronic intermittent hypoxia and is associated with an increased risk of all-cause mortality, including cancer mortality. Hepatocellular carcinoma (HCC) is the most common type of liver cancer, characterized by increasing incidence and high mortality. However, the link between HCC and OSA-related chronic intermittent hypoxia remains unclear. Herein, we used a diethylnitrosamine (DEN)-induced HCC model to investigate whether OSA-related chronic intermit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 41 publications
(43 reference statements)
0
4
0
Order By: Relevance
“…RT-qPCR Assay. Based on the research reported [29], approximately 100 mg of rat liver tissue from each group was repeatedly ground, and AML12 cells from each group were collected separately. Total RNAs were isolated from the samples with TRIzol (TAKARA; cat.…”
Section: Sirius Red Stainingmentioning
confidence: 99%
“…RT-qPCR Assay. Based on the research reported [29], approximately 100 mg of rat liver tissue from each group was repeatedly ground, and AML12 cells from each group were collected separately. Total RNAs were isolated from the samples with TRIzol (TAKARA; cat.…”
Section: Sirius Red Stainingmentioning
confidence: 99%
“…However, as tumors outgrow their blood supply over time, chronic hypoxia develops, with paradoxical adaptive cellular responses through the stabilization of HIFs and the resumption of transcriptional activation of genes involved in angiogenesis, cellular proliferation, and cell survival [20,36,37]. The upregulation of HIF-1α and VEGF in the setting of chronic hypoxia was observed in a preclinical study of HCC rat models, resulting in tumor growth [38,39]. Additionally, upregulating the expression of anti-apoptotic genes, such as B-cell lymphoma 2 (Bcl-2), desensitizes HCC cells to apoptosis [19,25].…”
Section: Molecular Pathways Of Hypoxiamentioning
confidence: 99%
“…Hypoxemia and its consequences should also be considered when treating patients using gases such as helium, xenon, and CO 2 [ 25 , 26 , 27 ]. Intermittent hypoxemia is a special situation [ 28 ]. The morphology of RBCs, specifically the stiffness and nanostructure of their membranes, can be altered in blood diseases, resulting in impaired cellular deformability [ 29 , 30 , 31 , 32 ].…”
Section: Introductionmentioning
confidence: 99%